PENGARUH KONSENTRASI SUKROSA TERHADAP KARAKTERISTIK MINUMAN PROBIOTIK SARI BUAH TERUNG BELANDA TERFERMENTASI DENGAN LACTOBACILLUS RHAMNOSUS SKG34 - Clarita Tampinongkol, Netta; Ayu Nocianitri, Komang; Ekawati, I Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 3 (2020): Jurnal ITEPA, 2020)
This research was conducted to determine the effects of sucrose concentration on characteristics of fermented tamarillo (Solanum betaceum Cav.) probiotic juice with L. rhamnosus SKG34. The Randomized Block Design was used with 5 treatment of sucrose concentration such as (0%, 3%, 6%, 9%, and 12%). The treatment was repeated 3 times so that were obtained 15 experimental units. Data were analyzed by ANOVA and DNMRT Test. The parameters observed included total LAB, total sugar, total acid, pH, and sensory acceptance of the resulting product were analyzed by a hedonic test on color, aroma, taste, and scoring test on color, as well as sourness and sweetness of the product, and overall acceptance. The results showed that the treatment of sucrose concentration on fermented tamarillo probiotic juice significantly affected the total LAB, total sugar, total acid, pH, color (score), taste (hedonic), sour taste and sweet taste (score), and overall acceptance, but no significant effect on color (hedonic) and aroma. The concentration of 9% sucrose produced the best characteristics of fermented tamarillo probiotic juice with total LAB 1.30 x 109 cfu/ml, total sugar 12.69%, total acid 3.08%, pH 3.61, the red color was preferred, the flavor slightly liked, the taste slightly sour and sweet was slightly preferred, and overall acceptance was preferred.